Fluorescent detection of uric acid through photoinduced electron transfer using luminol-terbium(III) nanoparticles synthesized via aggregation-induced fluorescence strategy. (January 2020) - Qi, Wenjing; Zhao, Maoyu; Fu, Yuling; He, Hongkun; Tian, Xue; Wu, Di; Zhang, Yan; Hu, Ping Ping
Abstract: Lanthanide coordination nanoparticles terbium(III) (Tb 3+ )-based fluorescent nanoparticles (luminol-Tb NPs) are synthesized via aggregation-induced fluorescence strategy. Fluorescence of luminol-Tb NPs is enhanced nearly 40 times compared with luminol, which is the effect of aggregation-induced fluorescence by Tb 3+ . Luminol-Tb NPs with high fluorescence is utilized in fluorescent "turn-off" detection of uric acid (UA) within 1 min from 0.1 to 50 μM with the limit of detection (LOD) of 28 nM. The fluorescence quenching effect may be ascribed to photoinduced electron transfer occurs from luminol-Tb NPs to UA. This fluorescent method exhibits high selectivity in UA detection towards metal ions, glucose, ascorbic acid, dopamine, creatinine, urea and cysteine. When it is also applied in detection of UA in serum samples, 5 μM, 10 μM and 30 μM UA are respectively added to serum samples and recoveries range from 97.5% to 101.3% in serum samples. It demonstrates the practical value of luminol-Tb NPs for UA detection in serum. Graphical abstract: Terbium(III) (Tb 3+ )-based nanoparticles are synthesized via aggregation-induced fluorescence strategy and utilized in fluorescent detection of uric acid through photoinduced electron transfer.Image 1 Highlights: Tb 3+ -based fluorescent nanoparticles (luminol-Tb NPs) are synthesized via aggregation-induced fluorescence. Fluorescence of luminol-Tb NPs is enhanced nearly 40 times compared with luminol. Luminol-Tb NPs are utilized in fluorescent "turn-off" detection of UA through photoinduced electron transfer. It is a fast detection within 1 min and the limit of detection of is 28 nM.